Hepatitis B Virus–Telomerase Reverse Transcriptase Promoter Integration Harnesses Host ELF4, Resulting in Telomerase Reverse Transcriptase Gene Transcription in Hepatocellular Carcinoma - Sze, Karen Man‐Fong (Hepatology, 2020)
BACKGROUND AND AIMS: Hepatitis B virus (HBV) integrations are common in hepatocellular carcinoma (HCC). In particular, alterations of the telomerase reverse transcriptase (TERT) gene by HBV integrations are frequent; however, the molecular mechanism and functional consequence underlying TERT HBV integration are unclear. APPROACH AND RESULTS: We adopted a targeted sequencing strategy to survey HBV integrations in human HBV‐associated HCCs (n = 95). HBV integration at the TERT promoter was frequent (35.8%, n = 34/95) in HCC tumors and was associated with increased TERT mRNA expression and more aggressive tumor behavior. To investigate the functional importance of various integrated HBV components, we employed different luciferase reporter constructs and found that HBV enhancer I (EnhI) was the key viral component leading to TERT activation on integration at the TERT promoter. In addition, the orientation of the HBV integration at the TERT promoter further modulated the degree of TERT transcription activation in HCC cell lines and patients’ HCCs. Furthermore, we performed array‐based small interfering RNA library functional screening to interrogate the potential major transcription factors that physically interacted with HBV and investigated the cis‐activation of host TERT gene transcription on viral integration. We identified a molecular mechanism of TERT activation through the E74 like ETS transcription factor 4 (ELF4), which normally could drive HBV gene transcription. ELF4 bound to the chimeric HBV EnhI at the TERT promoter, resulting in telomerase activation. Stable knockdown of ELF4 significantly reduced the TERT expression and sphere‐forming ability in HCC cells. CONCLUSIONS: Our results reveal a cis‐activating mechanism harnessing host ELF4 and HBV integrated at the TERT promoter and uncover how TERT HBV‐integrated HCCs may achieve TERT activation in hepatocarcinogenesis.